Shaping Students’ Writing Skills: The Study of Fundamental Aspects in Mastering Academic Writing - Ariyanti Ariyanti (Indonesian Journal of EFL and Linguistics, 2016)
Writing has become one of important skills in English language acquistion since a long time ago. Without leaving aside the importance of using active English to communicate, the passive one also plays important role to convey the message. Writing, as a way to explore our passive English is not merely intended to describe any topic without purposes. In this case, writing is a progressive activity. Oshima and Hogue (1997:2) explain the meaning of progressive in writing is when we want to start the first step to write about a certain topic, actually we have already known what we are going to write and how we explore it. After that, we read over our writing than we will do some corrections and also changes. In short, in order to have a better writing we should never stop only in one step. The more particular and specific urgency in writing is how to make our writing academic. This is what the most college students face in their writing tasks such as essays and final projects which become the requirement for them to finish their study in a university. In fact, academic writing is not as easy as the students think that they will just ask to write a passage freely. In this case, academic writing gives full description and complete guidance on how to make their writing sounds academic. So that is what the researcher tried to explained to the readers especially for students who need to shape their ability to in doing such academic writing.